已知函数 $f(x)=\left|x \mathrm{e}^x-a\right|-a x(\ln x+1)(a \in \mathbf{R})$.
(1) 若 $a=-1$, 证明: $f(x) \geqslant x\left(\mathrm{e}^x+2\right)$;
(2) 若 $f(x) > 0$ 对任意的 $x \in(0,+\infty)$ 恒成立, 求 $a$ 的取值范围.
【答案】 22. (1) 证明: 因为 $f(x)$ 的定义域为 $(0,+\infty)$, 所以若 $a=-1, f(x)=x \mathrm{e}^x+1+x(\ln x+1)$. $\cdots \cdots \cdots \cdots 1$ 分 要证 $f(x) \geqslant x\left(\mathrm{e}^x+2\right)$, 即证 $1+x(\ln x+1) \geqslant 2 x$, 即证 $\ln x+\frac{1}{x}-1 \geqslant 0$.
2 分
令 $h(x)=\ln x+\frac{1}{x}-1$, 所以 $h^{\prime}(x)=\frac{1}{x}-\frac{1}{x^2}=\frac{x-1}{x^2}$, 令 $h^{\prime}(x) > 0$, 解得 $x > 1$, 令 $h^{\prime}(x) < 0$, 解得 $0 < x < 1$, 所以 $h(x)$ 在 $(0,1)$ 上单调递减, 在 $(1,+\infty)$ 上单调递增,
所以 $h(x) \geqslant h(1)=0$, 所以 $f(x) \geqslant x\left(\mathrm{e}^x+2\right)$.
(2) 解: 若 $f(x) > 0$ 对任意的 $x \in(0,+\infty)$ 恒成立,
即 $\frac{\left|x \mathrm{e}^x-a\right|}{x}-a(\ln x+1) > 0$ 对任意的 $x \in(0,+\infty)$ 恒成立.
4 分
令 $g(x)=\frac{\left|x \mathrm{e}^x-a\right|}{x}-a(\ln x+1)$.
若 $a \leqslant 0$, 则 $g(x)=\mathrm{e}^x-a\left(\frac{1}{x}+\ln x+1\right)$,

由 (1) 知 $\ln x+\frac{1}{x}-1 \geqslant 0$, 所以 $\ln x+\frac{1}{x}+1 \geqslant 2$, 又 $a \leqslant 0$, 所以 $-a\left(\frac{1}{x}+\ln x+1\right) \geqslant 0$,
Х $\mathrm{e}^x > 0$, 所以 $g(x)=\mathrm{e}^x-a\left(\frac{1}{x}+\ln x+1\right) > 0$, 符合题意;
若 $a > 0$, 令 $u(x)=x \mathrm{e}^x-a(x > 0), u^{\prime}(x)=(x+1) \mathrm{e}^x > 0$ 在 $x \in(0,+\infty)$ 上恒成立, 所以 $u(x)$ 在 $(0,+\infty)$ 上单调递增, 又 $u(0)=-a < 0, u(a)=a\left(\mathrm{e}^a-1\right) > 0$,
所以存在唯一的 $x_0 \in(0, a)$, 使得 $u\left(x_0\right)=0$, 且 $a=x_0 \mathrm{e}^{x_0}$,
所以 $g(x)=\left\{\begin{array}{l}\frac{a}{x}-\mathrm{e}^x-a \ln x-a, 0 < x \leqslant x_0, \\ \mathrm{e}^x-\frac{a}{x}-a \ln x-a, x > x_0,\end{array}\right.$ 当 $0 < x \leqslant x_0$ 时, $g(x)=\frac{a}{x}-\mathrm{e}^x-a \ln x-a$,
所以 $g^{\prime}(x)=-\frac{a}{x^2}-\mathrm{e}^x-\frac{a}{x} < 0$, 所以 $g(x)$ 在 $\left(0, x_0\right]$ 上单调递减.
当 $x > x_0$ 时, $g(x)=\mathrm{e}^x-\frac{a}{x}-a \ln x-a$, 所以 $g^{\prime}(x)=\mathrm{e}^x-\frac{a}{x}+\frac{a}{x^2}$,
当 $x > x_0$ 时, $y=\mathrm{e}^x-\frac{a}{x}$ 在 $\left(x_0,+\infty\right)$ 上单调递增, 所以 $\mathrm{e}^x-\frac{a}{x} > \mathrm{e}^{x_0}-\frac{a}{x_0}=\mathrm{e}^{x_0}-\frac{x_0 \mathrm{e}^{x_0}}{x_0}=0$,
所以当 $x > x_0$ 时, $g^{\prime}(x)=\mathrm{e}^x-\frac{a}{x}+\frac{a}{x^2} > 0$, 所以 $g(x)$ 在 $\left(x_0,+\infty\right)$ 上单调递增,
所以 $g(x)_{\text {min }}=g\left(x_0\right)=-a\left(\ln x_0+1\right) > 0$, 解得 $0 < x_0 < \frac{1}{e}$.
设 $y=x \mathrm{e}^x, x \in\left(0, \frac{1}{\mathrm{e}}\right)$. 所以 $y^{\prime}=(x+1) \mathrm{e}^x > 0$ 在 $\left(0, \frac{1}{\mathrm{e}}\right)$ 上恒成立, 所以 $y=x \mathrm{e}^x$ 在 $\left(0, \frac{1}{\mathrm{e}}\right)$ 上单调递增, 所以 $a=x_0 \mathrm{e}^{x_0} \in\left(0, \frac{1}{\mathrm{e}} \mathrm{e}^{\frac{1}{\mathrm{e}}}\right)$, 即 $a \in\left(0, \mathrm{e}^{\frac{1}{\mathrm{e}}-1}\right)$. 综上所述, $a$ 的取值范围为 $\left(-\infty, \mathrm{e}^{\frac{1}{\mathrm{e}}-1}\right)$.


系统推荐